3D Scaffolds to Study Basic Cell Biology. Issue 26 (21st February 2019) - Hippler, Marc; Lemma, Enrico Domenico; Bertels, Sarah; Blasco, Eva; Barner‐Kowollik, Christopher; Wegener, Martin; Bastmeyer, Martin
Abstract: Mimicking the properties of the extracellular matrix is crucial for developing in vitro models of the physiological microenvironment of living cells. Among other techniques, 3D direct laser writing (DLW) has emerged as a promising technology for realizing tailored 3D scaffolds for cell biology studies. Here, results based on DLW addressing basic biological issues, e.g., cell‐force measurements and selective 3D cell spreading on functionalized structures are reviewed. Continuous future progress in DLW materials engineering and innovative approaches for scaffold fabrication will enable further applications of DLW in applied biomedical research and tissue engineering. Abstract : Among other techniques, direct laser writing (DLW) has emerged as a promising technology for realizing biofunctionalized 3D scaffolds mimicking the properties of the extracellular matrix. Results are reviewed based on DLW addressing basic biological questions, such as selective cell spreading or cell mechanics in a tailored 3D environment.